Software architecture-based adaptation for Grid computing - Shang-Wen Cheng; Garlan, D.; Schmerl, B.; Steenkiste, P.; Ningning Hu (11th International Symposium on High-Performance Distributed Computing (HPDC-11 2002), 2002)
Grid applications must increasingly self-adapt dynamically to changing environments. In most cases, adaptation has been implemented in an ad hoc fashion, on a per-application basis. This paper describes work which generalizes adaptation so that it can be used across applications by providing an adaptation framework. This framework uses a software architectural model of the system to analyze whether the application requires adaptation, and allows repairs to be written in the context of the architectural model and propagated to the running system. In this paper, we exemplify our framework by applying it to the domain of load-balancing a client-server system. We report on an experiment conducted using our framework, which illustrates that this approach maintains architectural requirements.